The pretensions of moral realism - Sinclair, Neil (Wiley-Blackwell, 2012)
Many philosophers argue that the face-value of moral practice provides presumptive support to moral realism. This paper analyses such arguments into three steps. (1) Moral practice has a certain face-value, (2) only realism can vindicate this face value, and (3) the face-value needs vindicating. Two potential problems with such arguments are discussed. The first is taking the relevant face-value to involve explicitly realist commitments; the second is underestimating the power of non-realist strategies to vindicate that face-value. Case studies of each of these errors are presented, drawn from the writings of Shafer-Landau, Brink and McNaughton, and from recent work in experimental metaethics. The paper then considers weak presumptive arguments, according to which both realist and non-realist vindications of moral practice are possible, but the realist vindications are more natural. It is argued that there is no sense of ‘natural’ available that can make these arguments work. The conclusion is that all extant presumptive arguments for moral realism fail.